Impacto de nanofertilizantes en la micorrización y crecimiento inicial de Medicago truncatula - Giachero, María Lorena; Marquez, Nathalie; Ranieri, Veronica Valeria; Ciacci, María Belén (Asociación Argentina Ciencia del Suelo (AACS), 2022)
Poster